Penggunaan Model Pembelajaran Berbasis Proyek terhadap Penguasaan Mufradat Siswa Negeri 1 Sungai Penuh - Ulinnuha, Nur Atika Rima; Muhammad Fadhil Husein (An Naba, 2024)
This study aims to examine the effectiveness of the Project Based Learning (PjBL) model on the vocabulary (mufradat) mastery of 10th-grade students at MA Negeri 1 Sungai Penuh. Vocabulary mastery is a crucial element in learning the Arabic language, as vocabulary forms the basis of effective communication and deep understanding of texts. This research uses an experimental method by comparing two classes: an experimental class using the PjBL model and a control class using conventional methods. The results show that students in the experimental class demonstrated a significant improvement in vocabulary mastery compared to students in the control class. The study concludes that the application of the PjBL model is effective in enhancing students' Arabic vocabulary mastery